Description Of The Results Of The Cytological Examination Of Pleural Fluid Using Giemsa Staining - Eva Sri Ayu Tarigan (Medistra Medical Journal (MMJ), 2023)
Many objects after being fixed and then glued with entellan or balsam become so transparent that their structure is not obvious when viewed with a microscope. To overcome this difficulty, in general, preparations are colored with dyes that can clarify their structure. Staining aims to sharpen or clarify various tissue elements, especially the cells, so that they can be distinguished and studied under a microscope. This research was conducted at the Anatomical Pathology Laboratory of Grandmed Lubuk Pakam Hospital in February 2020 - July 2020. The research design was descriptive. The population of this study were all pleural effusion fluid cytology preparations at the Anatomical Pathology Laboratory of Grandmed Lubuk Pakam Hospital. The sampling technique used is accidental sampling, namely the technique of determining the sample by chance. In this case, the samples found were 16 samples. The results showed that microscopic images of pleural fluid cytology preparations using Giemsa staining showed poor (43.75%) and good (56.25%) results. The results of this study are expected to be input for the Anatomical Pathology Laboratory about the description of the results of the pleural fluid cytology examination using Giemsa staining to improve service quality.